Interspecific Neighbor Stimulates Peanut Growth Through Modulating Root Endophytic Microbial Community Construction - Chen, Pin; He, Wei; Shen, Yi; Zhu, Lingyue; Yao, Xiangzhi; Sun, Ruibo; Dai, Chuanchao; Sun, Bo; Chen, Yan (Frontiers in Plant Science, 2022)
Plants have evolved the capability to respond to interspecific neighbors by changing morphological performance and reshaping belowground microbiota. However, whether neighboring plants influence the microbial colonization of the host’s root and further affect host performance is less understood. In this study, using 16S rRNA high-throughput sequencing of peanut (Arachis hypogaea L.) roots from over five years of mono- and intercropping field systems, we found that neighbor maize can alter the peanut root microbial composition and re-shape microbial community assembly. Interspecific maize coexistence increased the colonization of genera Bradyrhizobium and Streptomyces in intercropped peanut roots. Through endophytic bacterial isolation and isolate back inoculation experiments, we demonstrated that the functional potentials of available nutrient accumulation and phytohormones production from Bradyrhizobium and Streptomyces endowed them with the ability to act as keystones in the microbial network to benefit peanut growth and production with neighbor competition. Our results support the idea that plants establish a plant-endophytic microbial holobiont through root selective filtration to enhance host competitive dominance, and provide a promising direction to develop modern diversified planting for harnessing crop microbiomes for the promotion of crop growth and productivity in sustainable agriculture.